Lynch vs transcaruncular approach: optimizing access to the lateral frontal sinus. Issue 8 (14th May 2020) - Husain, Qasim; Banks, Catherine; Bleier, Benjamin S.
Abstract : Background: Visualization and instrumentation of the frontal sinus is not always possible with a Draf III or modified endoscopic Lothrop procedure (MELP), and external incisions can help augment exposure. We compare lateral frontal sinus access using only a MELP compared to the adjunctive transcaruncular approach and transcutaneous Lynch incision. Methods: Twelve cadaveric heads underwent thin‐cut computed tomography scanning. Measurement of the frontal beak, anteroposterior depth of the frontal sinus, and interorbital distance was performed. There were 4 specimens with poorly pneumatized frontal sinuses that were excluded from the study. Eight cadaveric heads (16 sides) were dissected and a MELP with bilateral transcaruncular and Lynch incisions for access to the lateral frontal sinus was performed. Under image guidance, measurements extended from the midline crista galli to the most lateral point of the frontal sinus visualized using a 0‐degree endoscope with straight suction and a 30‐degree endoscope with curved suction. Results: The proportion of the ipsilateral frontal sinus accessed through the contralateral nare with a 0‐degree endoscope and straight suction using a MELP only, a MELP with transcaruncular approach, and a MELP with Lynch incision, respectively, averaged 41.6%, 51.6%, and 58.9% on the right, and 48.9%, 47.1%, and 61.2% on the left. Using a 30‐degree endoscope and curved suction the proportion accessed using a MELP only, a MELP with transcaruncular approach, and a MELP with Lynch incision, respectively, increased to 76.1%, 62.6%, and 91.8% on the right, and 83.2%, 62.7%, and 88.7% on the left. Conclusion: Adjunctive external approaches can improve access and instrumentation of the frontal sinus when combined with a MELP.